Analisis Perkembangan Struktur Modal dan Keterkaitannya terhadap Harga Saham pada PT Bank Syariah Indonesia Tbk Periode 2021–2025 - Ramadanis Ramadanis; Nayla Permata Devi; Nur Hazizah; Marsya Vellinda Dwi Arini; Shalsabila Shalsabila; Salwa Salsabila; Rendi Resfinaldy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The capital market plays a vital role in the economy, where capital structure serves as an important indicator influencing investor perception and stock price stability, particularly in the case of PT Bank Syariah Indonesia Tbk following its merger. This research aims to describe the development of capital structure and stock price movements, as well as to interpret the tendency of the relationship between the two. The method applied is descriptive quantitative, utilizing secondary data from annual reports and capital market data. The analysis technique includes calculating the debt-to-equity ratio and observing stock price trends narratively. The results indicate that the company's capital structure is relatively stable, with the ratio fluctuating in the range of 2.02 to 2.47 times. On the other hand, stock prices showed dynamic and fluctuating movements throughout the observation period. Further analysis reveals that changes in capital structure do not always move in line with stock price movements, indicating the influence of external factors such as market sentiment and macroeconomic conditions. The implications of these findings suggest that management should continue to optimize the balance of funding to minimize financial risk, while also advising investors not to rely solely on capital structure ratios, but to consider other fundamental factors in making investment decisions.